Integrasi Nilai-nilai Kearifan Lokal dalam Manajemen Pendidikan Pesantren: Studi pada Dayah Raudhatul Ma’arif Al-Aziziyah Cot Trueng - Zulfikar, Zulfikar; Daud, Al Husaini M; Salabi, Agus Salim (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study focuses on local wisdom-based educational management at Dayah Raudhatul Ma’arif Al-Aziziyah Cot Trueng, one of the traditional Islamic educational institutions in Aceh. The background of this research is based on the importance of preserving and integrating local values into the pesantren education system to shape the character and leadership of students. The research employs a qualitative approach with data collection techniques including observation, in-depth interviews, and document analysis. The findings indicate that the implementation of educational management at this dayah successfully integrates local values, namely "ureung meudagang," which emphasizes entrepreneurial values such as hard work, honesty, and innovation, into the daily lives of students, and "beut-seumeubeut," which underscores the importance of continuous teaching and learning processes, instilling values of patience, perseverance, and social responsibility such as cooperation, mutual aid, and independence. These values are internalized through various management strategies, including a clear organizational structure, an integrative curriculum, and the central role of teachers in providing examples. This management not only strengthens students' identities but also makes a significant contribution to the preservation of local culture and the development of entrepreneurial potential among students. The implications of the research suggest that developing education based on local values can enrich the curriculum, strengthen pesantren management, and create an educational model that is contextual and relevant to community needs.